Discourse Markers in Political Speeches: Forms and Functions (Journal of the College of Education for Women, 2019)
Discourse markers are expressions used to connect sentences to what comes before or after and indicate a speaker's attitude to what he is saying.As linguistic items, they have important functions in discourses of various styles or registers. And being connective elements, discourse markers relate sentences, clauses and paragraphs to each other. "One of the most prominent function of discourse markers, however, is to signal the kinds of relations a speaker perceives between different parts of the discourse". (Lenk 1997: 2) Through political discourse, different types of discourse markers are used. This paper deals with the importance and functions of discourse markers and tries to shed light on the kinds of discourse markers used in political speech through analyzing the speech of the American president, Barack Obama, depending on Hyland and Tse’s (2004) classification of discourse markers; interpersonal and textual markers. The results show that these discourse markers function as means ofsocial interaction aimed at influencing the nation.